William Blake and the Body - Connolly, T. author. aut Link
XVII, 249 p.
Keywords: William Blake and the Body re-evaluates Blake's central image: the human form. In Blake's designs, transparent-skinned bodies passionately contort; in his verse, metamorphic bodies burst from each other in gory, gender-bending births. The culmination is an ideal body uniting form and freedom. Connolly explores romantic-era contexts like anatomical art, embryology, miscarriage and twentieth-century theorists like those of Kristeva, Douglas, Girard to provide an innovative new analysis of Blake's transformations of body and identity.